Transdiagnostic psychosocial interventions to promote mental health in forcibly displaced persons: a systematic review and meta-analysis - Schäfer, Sarah K; Kunzler, Angela M; Lindner, Saskia; Broll, Jan; Stoll, Marlene; Stoffers-Winterling, Jutta; Lieb, Klaus (Taylor & Francis, 2023)
Background: People forced to leave their homes, such as refugees and internally displaced persons, are exposed to various stressors during their forced displacement, putting them at risk for mental disorders. Objective: To summarize evidence on the efficacy of psychosocial interventions aiming to promote mental health and/or to prevent mental symptoms by fostering transdiagnostic skills in forcibly displaced persons of all ages. Method: Four databases and reference lists were searched for randomized controlled trials on interventions in this population on 11 March 2022. Thirty-six studies were eligible, 32 studies (comprising 5299 participants) were included in random-effects multilevel meta-analyses examining the effects of interventions on mental symptoms and positive mental health (e.g. wellbeing) as well as moderators to account for heterogeneity. OSF Preregistration-ID: 10.17605/OSF.IO/XPMU3 Results: Our search resulted in 32 eligible studies, with 10 reporting on children/adolescents and 27 on adult populations. There was no evidence for favourable intervention effects in children/adolescents, with 44.4% of the effect sizes pointing to potentially negative effects yet remaining non-significant. For adult populations, our meta-analyses showed a close-to-significant favourable effect for mental symptoms, M(SMD) = 0.33, 95% CI [–0.03, 0.69], which was significant when analyses were limited to high-quality studies and larger for clinical compared to non-clinical populations. No effects emerged for positive mental health. Heterogeneity was considerable and could not be explained by various moderators (e.g. type of control, duration, setting, theoretical basis). Certainty of evidence was very low across all outcomes limiting the generalizability of our findings. Conclusion: The present review provides at most weak evidence for an effect favouring transdiagnostic psychosocial interventions over control conditions for adult populations but not for children and adolescents. Future research should combine the imperative of humanitarian aid in face of major crises with studying the diverse needs of forcibly displaced persons to improve and tailor future interventions.
Keywords: Refugees; displacement;systematic review; meta-analysis; psychosocialintervention; transdiagnosti